Relación entre marketing interno y el compromiso organizacional de los trabajadores de una empresa pública de Lima - Torres Valladares, Manuel (2014)
The main purpose of the current investigation was to obtain a description of how the employees of a public enterprise of Lima perceive the internal marketing that develops on it and how this relates to their organizational commitment. A correlational descriptive design was used with a sample of 279 employees to whom two instruments of evaluation were applied: the Internal Marketing Questionnaire of Maria Bohnenberger and the Inventory of Organizational Commitment of Allen and Meyer. These instruments were submitted to the respective analyses that determined that the tests are valid and reliable. The results show that significant and positive correlations exist between internal marketing and organizational commitment in this sample of workers (r = 0.79). Moreover, it was found that the female workers obtain higher scores than the male workers in both internal marketing and organizational commitment.